CITOTOXICIDADE DE PECTINAS DO ALBEDO DE MARACUJÁ (Passiflora edulis flavicarpa) EM LINHAGENS TUMORAIS - Marenda, Flávia Roberta Buss (2015)
The passion fruit industrial use reach only 25% of the total fruit and passion fruit peel, representing 50% of the total, are discarded, but can be used in the extraction of pectin. Recent studies indicate that pectin, modified so as native, has antitumor activity. This study aimed to evaluate the cytotoxicity of pectin of passion fruit peel in tumor cell lines. Extraction has been made and the chemical modification of pectin of passion fruit peel, subjected to three different treatments. Both the raw material and pectin were characterized by specific analyzes. The cytotoxicity of untreated pectins, modified autoclaved and autoclaved were evaluated in tumor lines Jurkat, HeLa and HRT-18. The peel of passion fruit represented 54.7% of total fruit. The passion fruit peel flour bleached untreated and shown to be rich in soluble and insoluble fibers. The flour autoclaved pectin showed higher content of phenolic compounds; however, bleached pectin retained more phenolic compounds from the raw material. The modified pectins had a lower degree of methoxylation and lower molecular weight compared to native pectins, confirming the modification process. The best effect Cytotoxicity in Jurkat cells treated with autoclaved pectin modified with IC50 of 2.63 mg mL-1. The calculation of the selectivity index indicated that the modified autoclaved pectin has a low toxicity to healthy cells. In conclusion, the results demonstrate a potential antitumor promising for autoclaved modified pectin, that needs to be further exploited.